Industry standard architecture (ISA) based data acquisition card - Porquis, Lope Ben C. (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 2007)
This paper was addressed to the problem of producing an inexpensive local counterpart of a Data Acquisition Card that would serve as an interface between computer and the hardware prototype for real time hardware in-the-loop simulation. The project was developed following two stages: the experimental stage and prototype stage. The C language was used in testing and evaluating the device. The results of the evaluation showed that the device could sample around 1.5 kilo samples per second with greater accuracy if signals are samples at 100Hz or lower. The device yields a good noise performance. The overall cost of the project was around Php 5000.00.